NLRP6 Serves as a Negative Regulator of Neutrophil Recruitment and Function During Streptococcus pneumoniae Infection - Tao, Qi; Xu, Dongyi; Jia, Kaixiang; Cao, Xinrui; Ye, Chao; Xie, Sanlei; Hu, Dong-Liang; Peng, Lianci; Fang, Rendong (Frontiers in Microbiology, 2022)
Streptococcus pneumoniae (S. pneumoniae) is an invasive pathogen with high morbidity and mortality in the immunocompromised children and elderly. NOD-like receptor family pyrin domain containing 6 (NLRP6) plays an important role in the host innate immune response against pathogen infections. Our previous studies have shown that NLRP6 plays a negative regulatory role in host defense against S. pneumoniae, but the underlying mechanism is still unclear. The further negative regulatory role of NLRP6 in the host was investigated in this study. Our results showed that NLRP6-/- mice in the lung had lower bacterial burdens after S. pneumoniae infection and expressed higher level of tight junction (TJ) protein occludin compared to WT mice, indicating the detrimental role of NLRP6 in the host defense against S. pneumoniae infection. Transcriptome analysis showed that genes related to leukocytes migration and recruitment were differentially expressed between wild-type (WT) and NLRP6 knockout (NLRP6-/-) mice during S. pneumoniae infection. Also, NLRP6-/- mice showed higher expression of chemokines including C-X-C motif chemokine ligand 1 (CXCL1) and 2 (CXCL2) and lower gene expression of complement C3a receptor 1 (C3aR1) and P-selectin glycoprotein ligand-1 (PSGL-1) which are the factors that inhibit the recruitment of neutrophils. Furthermore, NLRP6-/- neutrophils showed increased intracellular bactericidal ability and the formation of neutrophil extracellular traps (NETs) during S. pneumoniae infection. Taken together, our study suggests that NLRP6 is a negative regulator of neutrophil recruitment and function during S. pneumoniae infection. Our study provides a new insight to develop novel strategies to treat invasive pneumococcal infection.